Regulation of food processing business in Pangasinan - Garcia, Patrizsa Dana P. (Virgen Milagrosa University Foundation : [s.n.], 2018)
The study aimed to determine the level of compliance of and awareness of the food processing businesses in Pangasinan as basis for the preparation of a project proposal for possible assistance to food processors. The study covered 30 food processing businesses in Pangasinan that are registered with the Department of Trade and Industry (DTI) as single proprietorship form of business organization. The quantitative survey method was used. A survey questionnaire was developed and used to gather data from the respondents. The study revealed the majority of respondents are into manufacturing business; sole proprietors with capitalization of not more than P3 Million; majority have less than five employees or workers; operating for less than three years; there are 37 food products available in the 30 food processing businesses in Pangasinan. The level of compliance of selected food processing businesses in Pangasinan as to government regulatory requirements and quality standards, they are compliant. The level of awareness of selected food processing businesses in Pangasinan as to government regulatory requirement is highly aware. The major problems encountered by the food processing business in Pangasinan are the following: compliance to the requirements is too costly, the requirements are too many to comply with; and license fees or other charges imposed by the regulations are too costly. The proposed intervention of the research is a project proposal that can be used by the food processing business organizations in seeking possible assistance to finance the training and seminars, construction of processing center and for the expenses for the processing of requirements from Food and Drug Administration and other regulatory requirements. It is therefore recommended that the project proposal be considered for compliance of food processing business to government regulatory requirements.
Bibliography: pages 124-127.
CHED-La Union
Keywords: Food industry and trade